Pemberian Lisensi Merek Tanpa Perjanjian Tertulis dalam Bisnis Hak Atas Kekayaan Intelektual - Gusti Ayu Mirah Aena Febiyanti; Ni Luh Mahendrawati; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2019)
Registered brands will get legal protection that can prevent others parties from using the brand without permission. Other parties can use other people’s brands by first holding a written license and applying for registration at the Directorate General of IPR’s trademark office. Application for recording license agreement is submitted to Directorate General of IPR through electronic and non-electronic media. Applicants complete the specified document. Then an examination of the documents is carried out. If the document has been declared complete and appropriate, the Minister records the license agreement in the general list of brands. Then recording the license agreement is announced in the official news of the brand. The legal consequences of the provision of brand licenses carried out in an unwritten manner, the agreement is null and void because it does not fulfill the elements in Article 1 number (18) UUM 2016 jo. Article 43 paragraph (2) UUM 206, and Article 5 paragraph (1) PP No. 36 of 2018 concerning Recording of Intellectual Property License Agreement. It is best for entrepreneurs to be careful in giving licenses to other parties and the Directorate General of Intellectual Property Rights should hold a socialization so that the licensing agreement is carried out in writing and is recorded in the Directorate General of IPR’s trademark office.